GPER-Deficient Rats Exhibit Lower Serum Corticosterone Level and Increased Anxiety-Like Behavior. (28th August 2020) - Zheng, Yi; Wu, Meimei; Gao, Ting; Meng, Li; Ding, Xiaowei; Meng, Youqiang; Jiao, Yingfu; Luo, Ping; He, Zhenquan; Sun, Tao; Zhang, Guohua; Shi, Xueyin; et al.
Abstract : Ample evidence suggests that estrogens have strong influences on the occurrence of stress-related mood disorders, but the underlying mechanisms remain poorly understood. Through multiple approaches, we demonstrate that the G protein-coupled estrogen receptor (GPER) is widely distributed along the HPA axis and in brain structures critically involved in mood control. Genetic ablation of GPER in the rat resulted in significantly lower basal serum corticosterone level but enhanced ACTH release in response to acute restraint stress, especially in the female. GPER -/- rats of either sex displayed increased anxiety-like behaviors and deficits in learning and memory. Additionally, GPER deficiency led to aggravation of anxiety-like behaviors following single-prolonged stress (SPS). SPS caused significant decreases in serum corticosterone in WT but not in GPER-deficient rats. The results highlight an important role of GPER at multiple sites in regulation of the HPA axis and mood.